Drinking water instead of apple juice or no drink results in greater odds of 4 to 7 co-occurring protective oral health factors within the hour - Cholera, Mimansa; Cape, Rowena; Tanbonliong, Thomas; Stookey, Jodi D. (Frontiers in Nutrition, 2025)
ObjectiveTo inform drinking water guidance and intervention, this randomized controlled trial tested the hypothesis that a standard serving of drinking water would normalize saliva insulin and improve caries risk factors to a greater extent, within 60 min, than no beverage or a standard serving of apple juice.MethodsAfter baseline saliva collection, 105 healthy children (5–10y), attending routine dental check-ups, were randomly assigned to receive 500 mL water, 200 mL apple juice, or no drink. Simple unblinded randomization was stratified by age-and-sex-specific BMI percentile (5–85th or >85th). Follow-up saliva was collected at 45–60 min and classified with respect to insulin<170 pg/mL, pH > 7.0, buffering>5.0, osmolality<70 mmol/kg, amylase<60 μ/mL, IgG > 10 μg/mL, IgA < 112 μg/mL, and the sum of protective factors. In intention-to-treat analyses, quantile regression models tested for drinking water effects on median oral health factors and logistic regression models tested for greater relative odds of normalized saliva insulin and protective factors after drinking water.ResultsDrinking water instead of apple juice resulted in a significantly lower median saliva insulin (172 vs. 364 pg/mL), 10 times greater relative odds of saliva insulin below 170 pg/mL (OR = 10.84, 95%CI: 3.86–30.49, p < 0.001), and 5 times greater relative odds of 4 to 7 co-occurring saliva factors that protect against tooth decay (OR = 4.98, 95%CI: 1.42–17.48, p < 0.012). Drinking water instead of apple juice significantly increased the relative odds of pH > 7.0, buffering capacity>5.0, alpha-amylase<60 u/mL, and IgG > 10 μg/mL. Drinking water instead of no drink resulted in significantly lower median saliva insulin (172 vs. 266 pg/mL), significantly greater odds of saliva osmolality <70 mmol/kg, IgA < 112 μg/mL, and 4 to 7 co-occurring protective factors (OR = 4.63, 95%CI: 2.90–7.34, p < 0.001).ConclusionDrinking water instead of apple juice or no drink significantly improved 4 to 7 caries risk factors, simultaneously, within 60 min. The results warrant drinking water intervention to promote oral health.